The Correlation Between Tamaddun Islāmiyyah and Pre-Islamic Arab - Maulana, Wildan Ichza; Kamalludin Sasmito (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This research was focused on the correlation of socio-political conditions of pre-Islamic Arab society and the formation of tamaddun Islamiyah. This research study is driven by the historical disintegration that developed in academic circles, where history is understood in various ways without a clear accentuation of the developing storyline. Thus, this study tries to reveal how there is a close correlation between pre-Islamic Arab historiography and the tamaddun Islamiyah project initiated by the Prophet Muhammad. This research was a descriptive-qualitative research using socio-historical and Islamic history (Tārīkh Tasyrī') to analyze the nature, character, and influence of civilization then interpret and generalize the historical facts that surround it. The sources of data were obtained from various historical literatures relevant to the research topic. The results of this study indicate that the correlation between tamaddun Islam and pre-Islamic Arab civilization is a project to abolish Ashabiyyah which is rooted in Arab society.